L’enfant de Mezmaiskaya (Caucase) examiné dans une double perspective paléogénétique et paléoanthropologique - Véronique Barriel; Anne-Marie Tillier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In 1993 a child skeleton was recovered from the Mezmaiskaya cave in the northern Caucasus. The excellent bone preservation has allowed direct absolute dating and mitochondrial DNA extraction (Golovanova et al. 1999; Ovchinnikov et al. 2000). The palaeogenetic interpretation is examined in the present article based on data available for modern humans (Anderson et al. 1981; HvrBase; http://www.hvrbase.de) and for three Middle Palaeolithic fossils from Germany (Feildhofer 1 and 2 ; Krings et al. 1997; Krings et al. 1999; Schmitz et al. 2002) and Croatia (Vindija-75-G3/h-203; Krings et al. 2000), which are attributed to the Neanderthal line and those of Pan paniscus and the four sub-species of Pan troglodytes (EMBL and GenBank). The question of the phylogenetic status of the Mezmaiskaya child is examined using both molecular analysis and anthropological arguments.